Molecular characterization of Spirometra isolates across the USA - Tiana L. Sanders; Caroline Sobotyk; Pablo D. Jimenez Castro; Amira Abdu; Jennifer Baade; Mindy Borst; Sriveny Dangoudoubiyam; Brooke A. Delcambre; Jeff M. Gruntmeir; Alice Lee; Christian Leutenegger; Cecilia Lozoya; et al. (Parasitology)
Spirometra is a genus of zoonotic cestodes with an ambiguous species-level taxonomic history. Previously, Spirometra mansonoides was considered the only species present in North America. However, recent molecular data revealed the presence of at least three distinct species in the USA: Spirometra sp. 2 and 3, and Spirometra mansoni. This study aimed to elucidate the diversity and potential host associations of Spirometra species among companion animals in the USA. Samples (N = 302) were examined from at least 13 host species, including mammals, amphibians and reptiles. Sample types included eggs isolated from faeces (n = 222), adult specimens (n = 71) and plerocercoids (n = 9) from 18 different states and 2 territories across the USA. Extracted genomic DNA was subjected to PCR targeting a fragment of the mitochondrial cytochrome c oxidase subunit 1 (cox1) gene. Generated sequences (n = 136) were included in a phylogenetic analysis. Spirometra mansoni was detected in domestic cats (n = 76), dogs (n = 12), a White’s tree frog (n = 1), a Cuban knight anole (n = 1), a green iguana (n = 1) and a serval (n = 1) across 15 states and Puerto Rico. Spirometra sp. 2 was found only in dogs (n = 3) from Florida and Spirometra sp. 3 was found only in cats (n = 41) from 17 states. All plerocercoid samples were consistent with S. mansoni. The results confirm that at least three distinct Spirometra species are present and established in companion animals, such as dogs and cats, and likely are using various native and exotic species as paratenic hosts within the USA.